Cloud detection for high-resolution remote-sensing images of urban areas using colour and edge features based on dual-colour models. Issue 20 (18th October 2018) - Huang, Wei; Wang, Yueyun; Chen, Xiu
ABSTRACT: In this article, the colour and edge features of clouds are proposed based on the analysis of a large number of cloudy high-resolution remote-sensing images of urban area. Using the cloud features, a cloud detection method based on dual-colour space is proposed. First, two candidate cloud regions maps are built based on hue–saturation–intensity model and blue, green, red model, respectively. According to the superposition analysis of the two maps, fine cloud regions map are obtained. After removing the fine cloud regions from the image, the image is linearly stretched to enhance the intensity of thin clouds around the fine cloud regions. In the stretched image, the thin cloud regions map is built with the threshold technique. Finally, the fine cloud regions map and the thin cloud regions map are combined to form the complete cloud regions map. The results of experiments and comparisons indicate that our algorithm has good accuracy and efficiency.